Quantity and Qualities: The Development and Extent of Transboundary Water Law in Africa - Lautze, Jonathan F.; Giordano, Mark (2006)
This article documents and analyzes the largest collection of transboundary water agreements related to Africa. Collection contents are categorized to provide insights into the evolution and geography of transboundary water law in Africa, and – when possible - to situate that law within a global context. The findings reveal that both historic and geographic factors have influenced African agreements. Historically, there is a trend toward increasing robustness generally consistent with global trends. Geographically, agreements vary by the degree and type of water scarcity in associated basins. The findings help answer questions related to current transboundary water management in Africa and provide guidanceforfuture institutional development.